(3GdYWGA GdLRjd aj cTa ZWGA GdJQSjds - (3CHhYGeQ eMeO Hf CMeO Hf YGeQ GdHdhj GdWQThTj GdSGdejs
(3ChdgG (B:s
(3GdHGH GdNGeS YTQ aj GdEgOGA hGdEJMGa hGdGSJOYGA hGdGSJRGQI hGdGSJLOGA hGdGYJPGQ hGdESYGa s
(3BNQgG (B:s
(3GdHGH Gdehaj YTQjf aj GdYjhf ef SGFQ Gdafhf hgh MSHfG hfYe Gdhcjd s
(3Ydi eG LGA ef GdJQSjd aj cJGH GHf YeQh GdoeSei HGdhLjRs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B39 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs